The Quality of Life Overview of the Sandwich Generation in Medan Baru District, Medan City - Ruth Evelonia Hariani Siburian; Fajar Utama Ritonga (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The sandwich generation phenomenon describes the condition of individuals of productive age who bear economic responsibility for two generations simultaneously, namely their parents and financially dependent family members. This condition has the potential to affect the quality of life of individuals in the sandwich generation, particularly in Medan Baru District, Medan City. This study aims to describe the quality of life of individuals in the sandwich generation in Medan Baru District, Medan City. The study employs a qualitative method with a descriptive approach. The research informants are individuals of productive age who play a role as part of the sandwich generation. Data were collected through in-depth interviews and observations and analyzed based on the WHOQOL indicators, which include physical health, psychological well-being, social relationships, and environmental aspects. The results indicate that individuals in the sandwich generation experience a decline in quality of life in several aspects. In terms of physical health, informants experience fatigue due to long working hours, as well as irregular and unhealthy sleep patterns. Psychologically, pressure in the form of anxiety and stress was found, which remains at a normal level and can be managed independently. The social relationships aspect shows disturbances in the form of low-quality personal relationships that are considered abnormal and unhealthy, as well as a tendency to delay romantic relationships, which is still considered normal. Meanwhile, in the environmental aspect, informants experience limitations in engaging in recreation and leisure activities; however, they maintain good and harmonious family relationships and receive positive responses from the surrounding environment.